Bariatric Surgical Treatment for Obese Adolescents and Children - Choudhury, Kamal M; Zafar, Sheikh Mohammad Abu (BIRDEM Medical Journal, 2016)
Like in adults, the prevalence of childhood and adolescent obesity is increasing globally. The consequences of severe obesity are serious and for that reason the World Health Organization has recognized obesity as a disease. Among the treatment options for obesity comprising dietary restriction, increased physical activities and weight-reduction surgery, only the last one provides a sustained and consistent weightloss in obese patients. Numerous recent studies have validated this fact in favor of bariatric surgeries. Although in spite of having been associated with considerable significant complications, these are gaining popularity particularly in morbid obesity. The justification of bariatric surgeries in children and adolescents is still a contentious issue especially in regards to their physiologic growth and development. In many advanced countries, pediatric bariatric surgeries are being done under strict guidelines including India; but in our country, it is still in conceptual stage. Here we present essentially a conceptual framework and clinical guideline for bariatric surgery in adolescents and children in this review. Birdem Med J 2015; 5(1) Supplement: 34-42